Evaluation and optimisation of the Tinnitus E-Programme, an internet-based intervention for tinnitus self-management - Greenwell, Kate (2017)
Internet-based self-management interventions have the potential to reduce the current disparity in access to psychological support for people with tinnitus. One example is the Tinnitus E-Programme, which was developed in the United Kingdom to support self-management in people with tinnitus. Although freely available online, there was little understanding of how the intervention is used, its active ingredients, how it works, the circumstances in which it works best, and whom it works best for. This PhD aimed to address these issues by evaluating and optimising the Tinnitus E-Programme.